As the wicked watch - Hall, Tamron; Taylor, T. Shawn (Hall, Tamron. Jordan Manning novel., 2021)
The first in a thrilling new series from Emmy Award-winning TV Host and Journalist Tamron Hall, As The Wicked Watch follows a reporter as she unravels the disturbing mystery around the deaths of two Black girls; the work of a serial killer terrorizing Chicago. When crime reporter Jordan Manning leaves her hometown in Texas to take a job at a television station in Chicago, she's one step closer to her dream: a coveted anchor chair on a national network. Jordan is smart and aggressive, with unabashed star-power, and often the only woman of color in the newsroom. Her signature? Arriving first on the scene--in impractical designer stilettos. Armed with a master's degree in forensic science and impeccable instincts, Jordan has been able to balance her dueling motivations: breaking every big story--and giving a voice to the voiceless. From her time in Texas, she's covered the vilest of human behaviors but nothing has prepared her for Chicago. Jordan is that rare breed of a journalist who can navigate a crime scene as well as she can a newsroom--often noticing what others tend to miss. Again and again, she is called to cover the murders of Black women, many of them sexually assaulted, most brutalized, and all of them quickly forgotten. All until Masey James--the story that Jordan just can't shake, despite all efforts. A 15-year-old girl whose body was found in an abandoned lot, Masey has come to represent for Jordan all of the frustration and anger that her job often forces her to repress. Putting the rest of her work and her (fraying) personal life aside, Jordan does everything she can to give the story the coverage it desperately requires, and that Black children rarely receive. Jordan is convinced that there's a serial killer on the loose and he's hiding in plain sight.